Management of Public Transportation Infrastructure Assets by the Surabaya City Transportation Department to Support Public Services - Amelia Nur Rahmadani; Singgih Manggalaou (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Infrastructure and transportation asset management is a strategic aspect in supporting the quality of public services, especially in metropolitan cities with high mobility levels such as Surabaya. The increasing number of residents and motorized vehicles demands the availability and management of transportation assets that are effective, efficient, and sustainable. This study aims to analyze the management of infrastructure and transportation assets implemented by the Surabaya City Transportation Agency and its relationship to the quality of public transportation services. The research method used is qualitative with a descriptive approach. Data collection was conducted through interviews, observation, and documentation, using the asset management cycle analysis framework according to Mahmudi (2010) and referring to the regulation of the Minister of Home Affairs Regulation Number 7 of 2024 concerning Management of Regional Property. The results of the study indicate that infrastructure and transportation asset management at the Surabaya City Transportation Agency has generally been implemented according to the stages of planning, procurement, use, security, maintenance, and disposal of assets. However, several obstacles are still found, including inequality in the distribution of transportation assets, limited up-to-date asset data, and asset maintenance that is not fully preventive and risk-based. These conditions have implications for the suboptimal quality of public transportation services in several areas of Surabaya. Therefore, improving the accuracy of asset data, strengthening the maintenance system, and needs-based and priority-based planning are important steps to improve the effectiveness of asset management and the quality of public transportation services in a sustainable manner.